Pengaruh Karakteristik Klien dan Kantor Akuntan Publik Terhadap Audit Delay di Indonesia - Denis Annisa; Ni Nyoman Alit Triani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to study the audit delay phenomenon that occurs in trading, service and investment companies listed on the Indonesia Stock Exchange for the period 2018-2022. This research uses quantitative methods. The type of data used is secondary data sourced from audited financial reports from 2018-2022. The sample in this study was taken from data on trading, service and investment sector companies listed on the IDX. The data analysis technique in this study uses multiple linear regression tests. The results of this study state that the going concern audit opinion variable has an effect on audit delay, while the solvency variable, company size, audit tenure, public accounting firm size, and KAP industry specialization have no effect on audit delay.